Persistent effects of fragmentation on tropical rainforest canopy structure after 20 yr of isolation - Almeida, Danilo Roberti Alves de; Stark, Scott C.; Schietti, Juliana; Camargo, José Luís Campana; Amazonas, Nino Tavares; Görgens, Eric Bastos; Rosa, Diogo M.; Smith, Marielle N.; Valbuena, Rubén; Saleska, Scott Reid; Andrade, Ana C.S.; Mesquita, Rita de Cássia Guimarães; et al. (Ecological Applications, 2019)
Assessing the persistent impacts of fragmentation on aboveground structure of tropical forests is essential to understanding the consequences of land use change for carbon storage and other ecosystem functions. We investigated the influence of edge distance and fragment size on canopy structure, aboveground woody biomass (AGB), and AGB turnover in the Biological Dynamics of Forest Fragments Project (BDFFP) in central Amazon, Brazil, after 22+ yr of fragment isolation, by combining canopy variables collected with portable canopy profiling lidar and airborne laser scanning surveys with long-term forest inventories. Forest height decreased by 30% at edges of large fragments (>10 ha) and interiors of small fragments (<3 ha). In larger fragments, canopy height was reduced up to 40 m from edges. Leaf area density profiles differed near edges: the density of understory vegetation was higher and midstory vegetation lower, consistent with canopy reorganization via increased regeneration of pioneers following post-fragmentation mortality of large trees. However, canopy openness and leaf area index remained similar to control plots throughout fragments, while canopy spatial heterogeneity was generally lower at edges. AGB stocks and fluxes were positively related to canopy height and negatively related to spatial heterogeneity. Other forest structure variables typically used to assess the ecological impacts of fragmentation (basal area, density of individuals, and density of pioneer trees) were also related to lidar-derived canopy surface variables. Canopy reorganization through the replacement of edge-sensitive species by disturbance-tolerant ones may have mitigated the biomass loss effects due to fragmentation observed in the earlier years of BDFFP. Lidar technology offered novel insights and observational scales for analysis of the ecological impacts of fragmentation on forest structure and function, specifically aboveground biomass storage. © 2019 by the Ecological Society of America
Keywords: Aboveground Biomass; Canopy Architecture; Carbon Sequestration; Ecosystem Function; Environmental Degradation; Forest Dynamics; Habitat Fragmentation; Land-use Change; Leaf Area; Lidar; Project Management; Rainforest; Succession; Temporal Analysis; Tropical Forest; Turnover; Vegetation Structure; Amazonas; Ecosystem; Forest; Rainforest; Tree; Tropic Climate; Ecosystem; Forests; Rainforest; Trees; Tropical Climate